Rhetorical Discussion On "See Who Wants To Be President Of Nigeria" And The Impact Of Language On Politics And Communication/Advertising In The Era Of Change Agenda - Abalaka, J.N; Ajiteru,S.A.R; Sulaiman T.H (International Journal of Social Welfare and Family Law, 2025)
Building agreement and influencing public opinion need effective communication. As a means of expressing ideas, language creates emotions that are used for political advantages during an electoral campaign. Human existence and the maintenance of connections depend on communication, a complex process. In actuality, human interactions are lubricated by this substance. Despite its importance, communication has two sides and can be applied either favorably or unfavorably. From the standpoint of its capacity for complexity, Boulton (2019, p. 41) pointed to the negative social intent of language. She also noted that language is frequently employed to deceive rather than to communicate. Human existence and the maintenance of connections depend on communication, a complex process. In actuality, human interactions are lubricated by this substance. Despite its importance, communication has two sides and can be applied either favorably or unfavorably. According to Boulton (1978, p. 41), from the standpoint of language's capacity for complexity to the detrimental societal intent of language. She also noted that language is frequently employed to deceive rather than to communicate. Therefore, this discourse examines how the political advertisement "See who wants to be President of Nigeria" exposed ignorance and ineptitude as unacceptable in a moral and democratic society such as Nigeria. It is a political communication activity that uses word choice and language as a means of rejecting a candidate in the April 2015 Nigerian presidential election.